2004
DOI: 10.1164/rccm.200309-1248oc
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Bacteremia in Patients with Community-Acquired Pneumonia

Abstract: It is recommended that blood cultures be performed on all patients admitted to the hospital with pneumonia. Questions regarding the cost-effectiveness of this practice have emerged. We used data on 13,043 Medicare patients hospitalized with pneumonia to determine predictors of bacteremia. Predictors included recent antibiotic treatment, liver disease, and three vital-sign and three laboratory abnormalities. Patients were stratified into three groups on the basis of the likelihood of bacteremia. We then created… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
156
3
14

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(185 citation statements)
references
References 26 publications
12
156
3
14
Order By: Relevance
“…Very few subjects had positive blood or sputum cultures and cultures were not universally drawn, a situation that is typical for observational studies of CAP (35,36). Consequently, we could not reliably determine whether coagulation abnormalities varied by presence of bacteremia or by type of infecting organism.…”
Section: Discussionmentioning
confidence: 97%
“…Very few subjects had positive blood or sputum cultures and cultures were not universally drawn, a situation that is typical for observational studies of CAP (35,36). Consequently, we could not reliably determine whether coagulation abnormalities varied by presence of bacteremia or by type of infecting organism.…”
Section: Discussionmentioning
confidence: 97%
“…8 Because health care costs have exceeded increases in general goods and services, adjusting the results of Bates et al 3 using the Consumer Price Index likely underestimated the projected cost of the false-positive cultures. This limitation likely accounts for the observation that the difference in actual charges for our patients between those who did and those who did not have false-positive blood cultures was greater than the cost of these falsepositive cultures as estimated by extrapolating from the data of Bates et al 3 Given the magnitude of the financial difference we observed, however, we suggest that this difference is not of sufficient size to alter our conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Prediction rules to reduce blood culture testing have been developed for patients with community-acquired pneumonia, but the rules only reduced the number of cultures by 37% and, more importantly, left 11% of true bacteremias undetected. 8 Reducing contaminants would have no effect on the detection of true positives, whereas any prediction rule would inevitably increase the risk of missing true bacteremia in at least a fraction of patients. Second, methods aimed at reducing contaminants can be implemented immediately, whereas deriving a prediction rule would take years to develop and test before it could be utilized.…”
Section: Discussionmentioning
confidence: 99%
“…(16)(17)(18) We defined a clinically significant positive culture based on published guidelines and prior literature. (26)(27)(28)(29)(30)(31)(32)(33) For example, single blood cultures that yielded coagulase negative staphylococci, and sputum cultures that yielded normal oral flora were not counted as clinically significant. We defined severe sepsis as infection plus acute organ dysfunction following international consensus criteria.…”
Section: Methods Of Measurementmentioning
confidence: 99%